2020
DOI: 10.1039/c9an02491c
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared spectroscopic assessment of loosely and tightly bound cortical bone water

Abstract: NIR spectroscopy can differentiate water loosely bound to bone tissue, and tightly bound to either collagen or mineral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Analysis of specific second derivative NIR peak intensities and ratios allows quantification of several parameters directly associated with water and protein content 40 . Spectral absorbance peaks of water are observed at 5300, 7100 and 8600 cm -1 , with each peak related to water molecules present in different tissue environments, such as free and hydrogen-bound tissue water 20,22,[40][41][42][43][44][45][46] . Their relative intensities reflect differences in tissue type and composition 22 , and thus, the empirical evaluation of the water peak ratios may inform changes in molecular environments within the TEC, and correlations to TEC construct quality and related in vivo repair tissue quality.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of specific second derivative NIR peak intensities and ratios allows quantification of several parameters directly associated with water and protein content 40 . Spectral absorbance peaks of water are observed at 5300, 7100 and 8600 cm -1 , with each peak related to water molecules present in different tissue environments, such as free and hydrogen-bound tissue water 20,22,[40][41][42][43][44][45][46] . Their relative intensities reflect differences in tissue type and composition 22 , and thus, the empirical evaluation of the water peak ratios may inform changes in molecular environments within the TEC, and correlations to TEC construct quality and related in vivo repair tissue quality.…”
Section: Discussionmentioning
confidence: 99%
“…Research has largely been focused on the material level property changes directly associated with the altered collagen followed by a focus on the poor mineral quality ( Camacho et al, 2003 ; Surowiec et al, 2020 ). Water, particularly loosely and tightly bound collagen-related water, is hypothesized to play a role in governing bone health in OI through supporting formation and maintenance of collagen structure and possibly mineralization ( Ailavajhala et al, 2020 ; Kramer et al, 2000 ). Despite this link, little is known about how bone water is altered under OI conditions.…”
Section: Bone Water With Age and Diseasementioning
confidence: 99%
“…In bone, water molecules can occupy different compartments, such as within pores (free water), loosely bound to protein and mineral surfaces or tightly bound between collagen chains and within the mineral crystal lattice. Recently, Ailavajhala et al [ 47 ] showed that NIR spectroscopy can be applied to differently assess both loosely and tightly bound water in bone. They used a variety of sample preparation procedures (dehydration, deuteration, demineralization, denaturing) to regulate composition and molecular environments of cortical human bone samples.…”
Section: Application Of Vibrational Spectroscopy For Connective Timentioning
confidence: 99%
“…Typical absorbance bands of relevance to the analysis of NIR spectra of connective tissues [41][42][43][44][45][46][47][48][49]…”
mentioning
confidence: 99%